Structural analysis and hyperthermia effect of Fe3+/Ni2+ co-substitutions in β-Ca3(PO4)2 - Singh R.K.; Srivastava M.; Prasad N.K.; Kannan S. (My University, 2025)
The study investigates co-substitutions of Fe3+ and Ni2+ at the β-Ca3(PO4)2 structure for applications in hyperthermia. A detailed structural analysis, magnetic properties and the consequential hyperthermia effect due to the Fe3+ and Ni2+ co-substitutions at the β-Ca3(PO4)2 structure are studied. The structural analysis affirms the ability of β-Ca3(PO4)2 to host 12.55 mol. % Ni2+ and an equal share of ∼6.25 mol. % of Ni2+ and Fe3+ co-substitutions without significant structural distortions. Both the Ni2+ and Fe3+ prefer to occupy the six-fold co-ordinated Ca2+(5) site of β-Ca3(PO4)2 structure. Fe3+/Ni2+ co-substitutions in β-Ca3(PO4)2 display superior magnetic features and also show pronounced hyperthermia effect than Ni2+ only substitutions. Ni2+ presence at higher concentration elicit cytotoxic effects while its existence at lower concentration in Fe3+/Ni2+ co-substitutions display negligible toxicity. © 2017 Elsevier B.V.